Fraud threats: How organization improves the anti-fraud team quality? - Fajri, Kharisma Fatmalina; Hendi Yogi Prabowo (Jurnal Akuntansi dan Auditing Indonesia, 2024)
This study aims to discover how the Indonesian Local Government Rural Bank improves the quality of the anti-fraud team to prevent and detect fraud based on a mechanism of the anti-fraud strategy issued by Bank Indonesia. A qualitative analysis approach was applied 12 semi-structured interviews with the anti-fraud team and related officers. The content analysis approach supported by NVivo software and has discovered several required competencies and competencies already developed by the organization’s anti-fraud team for fraud prevention and detection. This study provides a detailed discussion of how these competencies are used in the anti-fraud mechanism by identifying the gaps between the required competencies and developed competencies to give recommendations for the organization to enhance the quality of the anti-fraud team in conducting fraud prevention and detection.